Prevalence of the Prothrombin Gene Variant (nt20210A) in Venous Thrombosis and Arterial Disease - Arruda, Valder R; Annichino-Bizzacchi, Joyce M; Gonçalves, Marilda S; Costa, Fernando F (Thrombosis and Haemostasis, 1997)
The prothrombin gene variant resulting form a G→A transition at position 20210 has been described as a common genetic risk factor for venous thrombosis. However, the risk for developing arterial disease is unknown. In this investigation, we studied 116 patients with venous thrombosis and 71 with arterial disease, all of whom were compared with 295 controls. Additionally, we also investigated the distribution of the prothrombin alleles among African descendents and Amazonian Indians from Brazil. The prevalence of 0.7% for 20210A allele in the control group increased to 4.3% (P = 0.021) among patients with venous thrombosis. There was also a high prevalence of the mutated allele in a selected arterial disease group (5.7%) without hyperlipoproteinemia, hypertension, and diabetes mellitus when compared to the controls (P = 0.013). Heterozygotes for the allele 20210A were common among individuals of African descent (2%) and rare among Indians. These data support the hypothesis that the prothrombin variant is a risk factor for venous thrombosis and suggest that it may also be a risk factor for arterial disease.